Common Fixed Points for Maps on Topological Vector Space Valued Cone Metric Spaces. (5th January 2010) - Beg, Ismat; Azam, Akbar; Arshad, Muhammad
Abstract : We introduced a notion of topological vector space valued cone metric space and obtained some common fixed point results. Our results generalize some recent results in the literature.